Economic Development, Technological Change, and Growth: The Growth Spiral: Money, Energy, and Imagination in the Dynamics of the Market Process - Perla, Jesse (Journal of Economic Literature, 2013)
Jesse Perla of University of British Columbia reviews, “The Growth Spiral: Money, Energy, and Imagination in the Dynamics of the Market Process” by Hans Christoph Binswanger. The Econlit abstract of this book begins: “Revised translation of Die Wachstumsspirale (2006). Presents a new theoretical approach to understanding the modern economy, focusing on its dynamic aspects. Discusses the difference between market and barter—money and the making of markets; capital and the firm—the firm as the engine of the market process; money and money creation in a two-stage banking system; the development of the theories of production—valid insights and shortcomings; production involving nature and imagination; income distribution in the process of growth; the move from the theory of growth to the theory of the growing economy; the economic process as a growth spiral; the increase of the present value of profits as the growth impetus; the avoidance of losses as the growth imperative; and growth opportunities and growth obstacles—the role of the state. Binswanger is with the Institute for Economy and the Environment at the University of St. Gallen.”